Microfundamentos das capacidades dinâmicas para o desenvolvimento de atividades de inovação orientadas à sustentabilidade: um estudo em projetos de uma organização do setor elétrico - Silva, Irlanda Mayra Medeiros da (2023)
Corporate and institutional debates on sustainable development within organizations have taken center stage in large companies, driven by stakeholder demands for ESG (Environmental, Social, and Governance) standards. In response, sustainability-oriented innovations (SOIs) have emerged as crucial adaptations, aimed at creating both social and environmental value while ensuring financial returns. The microfoundations (sensing, seizing, and reconfiguration) of dynamic capabilities (CD) serve as guiding principles in the strategic market, facilitating the transformation and propagation of resources and competences to foster these innovations. Despite extensive literature focusing on various types of innovations, such as environmental, social, and sustainable, there remains a gap in integrating studies that examine SOI activities (Operational Optimization, Organizational Transformation, and Systems Construction) from the perspective of dynamic capability microfoundations. Additionally, there is limited understanding of how these microfoundations of dynamic capabilities influence the development of such activities within business projects. To address these gaps, this study employs the theoretical lens of DC microfoundations along with sustainability-oriented innovation activities. The primary objective is to analyze how DC microfoundations contribute to the advancement of sustainability-oriented innovation activities. To achieve this, a comprehensive literature analysis was conducted, identifying 19 microfoundations and 19 SOI activities. This information played a pivotal role in constructing the conceptual framework, which was subsequently validated through case studies involving four projects within an organization operating in the energy industry. Data for the case studies were collected through semi-structured interviews and project report analyses. These data were transcribed and then subjected to content analysis. The findings reveal a strong influence of the microfoundations of detection, apprehension, and reconfiguration on SOI activities, particularly in the context of Operational Optimization (OO) and Organizational Transformation (TO). Based on this empirical evidence, 19 research propositions were formulated, illustrating both strong and weak relationships between microfoundations and SOI activities. This study's contributions encompass the development and refinement of the framework, empirical research propositions, and the advancement of literature in the field. Moreover, it successfully integrates microfoundations themes of dynamic capabilities with perspectives on SOI activities.